2021
DOI: 10.3389/fvets.2021.667425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Maltol on Innate Immunity, Gut Health, and Growth Performance of Broiler Chickens Challenged With Eimeria maxima

Abstract: Two studies were conducted to evaluate the effects of maltol as a postbiotic on innate immunity, gut health, and enteric infection. In the first study, an in vitro culture system was used to evaluate the effects of maltol on the innate immune response of chicken macrophage cells (CMC), gut integrity of chicken intestinal epithelial cells (IEC), anti-parasitic activity against Eimeria maxima, and differentiation of quail muscle cells (QMC) and primary chicken embryonic muscle cells (PMC). All cells seeded in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…With the development of "omics" technologies related to the investigation of gut health, the term "postbiotics" was coined and defined as a novel class of feed additives that are generally produced by beneficial gut microbes and which exert a positive influence on host health. In a recent in vivo feeding trial, the dietary feeding of Bacillus subtilis 1781 strain induced an alteration of chicken gut metabolites which was associated with the growth-and immune-promoting effects of B. subtilis probiotics [169]. Interestingly, among the highly altered gut metabolites, maltol was one of the significantly increased metabolites that mediated various physiological functions associated with antioxidant and anti-inflammatory activities.…”
Section: Probioticsmentioning
confidence: 98%
See 1 more Smart Citation
“…With the development of "omics" technologies related to the investigation of gut health, the term "postbiotics" was coined and defined as a novel class of feed additives that are generally produced by beneficial gut microbes and which exert a positive influence on host health. In a recent in vivo feeding trial, the dietary feeding of Bacillus subtilis 1781 strain induced an alteration of chicken gut metabolites which was associated with the growth-and immune-promoting effects of B. subtilis probiotics [169]. Interestingly, among the highly altered gut metabolites, maltol was one of the significantly increased metabolites that mediated various physiological functions associated with antioxidant and anti-inflammatory activities.…”
Section: Probioticsmentioning
confidence: 98%
“…Probiotics are live microbial feed supplements which beneficially affect the host animal by improving its intestinal microbial balance. Prebiotics, by contrast, are non-digestible feed ingredients that beneficially affect the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the gut [169][170][171]. Synergetic combinations of probiotics and prebiotics are known as synbiotics.…”
Section: Probioticsmentioning
confidence: 99%
“…We therefore evaluated the effects of ICOOH on muscle cell growth by using QMCs and PMCs in vitro . In the present study, we used different FBS concentrations (0.5% FBS in QMCs and 2% FBS in PMCs) to induce myogenic differentiation as in previous studies ( 50 ). In the current study, the MyoG level, when using the lowered FBS concentration, was elevated, thus supporting MyoG as a differentiation marker.…”
Section: Resultsmentioning
confidence: 99%
“…The major flavonols, such as quercetin, kaempferol, isorhamnetin, and galangin, were found to exhibit anti-inflammatory activity [ 29 , 31 ]. Maltol exerts a significant liver protection effect, and possesses anti-inflammatory and antiapoptotic actions [ 32 ]. Some studies demonstrated that bavachinin, nobiletin, and 3′-deoxysappanone B regulate the production of several cytokines as well as inflammatory mediators in activated macrophages and various other cell types [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maltol exerts a significant liver protection effect, and possesses anti-inflammatory and antiapoptotic actions [ 32 ]. Some studies demonstrated that bavachinin, nobiletin, and 3′-deoxysappanone B regulate the production of several cytokines as well as inflammatory mediators in activated macrophages and various other cell types [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Consequently, we evaluated whether these components of Pj-EE-CF could be responsible for its anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%